EFFECT OF NON PHARMACOLOGICAL INTERVENTION ON DIABETIC COMPLICATION IN PATIENT WITH TYPE 2 DIABETES MELLITUS: A SYSTEMATIC REVIEW - Sembiring Meliala, Richard Sejahtera (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Because of this, doctors and other healthcare professionals face the challenge of treating a significant number of diabetic patients in their day-to-day clinical practice. Because of this, it is imperative for them to be equipped with the knowledge and skills necessary to deal with situations such as these. Type 1 diabetes mellitus, commonly known as T1DM, and type 2 diabetes mellitus are the most prevalent kinds of diabetes that are diagnosed in clinical settings. Other forms of diabetes, such as gestational diabetes, are less common (also known as T2DM). Nevertheless, there is a very small percentage of people who also suffer from other forms of diabetes. Some of the lifestyle changes that are believed to be helpful in preventing type 2 diabetes mellitus or delaying the onset of the condition include eating a healthy, well-balanced diet, keeping a healthy body weight, engaging in regular physical activity, breaking the habit of leading a sedentary lifestyle, and staying away from tobacco use. Findings from the Diabetes Prevention Program (DPP) suggest that obtaining and keeping a healthy weight is one of the most essential things that can be done to lower one's risk of acquiring diabetes. Patients diagnosed with diabetes mellitus have access to a variety of non-pharmacological intervention strategies, including changes in their diet and lifestyle, which can be used to help reduce the risk of diabetic complications. The patient education that is provided can also be incorporated into reminders for the patient.